Calcolo della derivata seconda

Calcolare la derivata seconda delle seguenti funzioni: Esercizio 1 \[ f\left(x\right)=\sqrt{x} \] Soluzione \[ f’\left(x\right)=\frac{1}{2\sqrt{x}} \] Derivando ulteriormente: \[ f”\left(x\right)=\left(0-2\frac{1}{2\sqrt{x}}\right)\frac{1}{\left(2\sqrt{x}\right)^{2}} \] \[ f”\left(x\right)=-\frac{1}{\sqrt{x}}\cdot\frac{1}{4x} \] \[ f”\left(x\right)=-\frac{1}{4x\sqrt{x}} \] Esercizio 2 \[ f\left(x\right)=\frac{x^{3}}{x+1} \] Soluzione \[ f’\left(x\right)=\frac{3x^{2}\left(x+1\right)-x^{3}}{\left(x+1\right)^{2}} \] \[ f’\left(x\right)=\frac{3x^{3}+3x^{2}-x^{3}}{\left(x+1\right)^{2}} \] \[ f’\left(x\right)=\frac{2x^{3}+3x^{2}}{\left(x+1\right)^{2}} \] Derivando ulteriormente: \[ f”\left(x\right)=\frac{\left(6x^{2}+6x\right)\left(x+1\right)^{2}-\left(2x^{3}+3x^{2}\right)\cdot2\left(x+1\right)}{\left(x+1\right)^{4}} \] \[ f”\left(x\right)=\frac{\left(x+1\right)\left[\left(6x^{2}+6x\right)\left(x+1\right)-\left(4x^{3}+6x^{2}\right)\right]}{\left(x+1\right)^{4}} \] \[ f”\left(x\right)=\frac{6x^{3}+6x^{2}+6x^{2}+6x-4x^{3}-6x^{2}}{\left(x+1\right)^{3}} \] \[ f”\left(x\right)=\frac{2x^{3}+6x^{2}+6x}{\left(x+1\right)^{3}} […]